الإطار الوظيفي للسلطة الوطنية المستقلة للانتخابات - بوفلغة, بلال; بوطيب, صفاء (University of Eloued جامعة الوادي, 2020)
تعتبر السلطة الوطنية المستقلة للانتخابات آلية جديدة دائمة، أستحدثها المشرع الجزائري بموجب القانون العضوي 19 – 07، بهدف ضمان شفافية ونزاهة العملية الانتخابية عبر كافة مراحلها بدء من مراجعة القوائم الانتخابية إلى غاية إعلان النتائج ولقد خص المشرع الجزائري السلطة المستقلة بسلطات واسعة وغير محدودة تشمل الإشراف والتنظيم والرقابة على العملية الانتخابية ومدى مطابقتها للأحكام القانونية، ولقد منح المشرع الجزائري هذه السلطة جملة من الضمانات لتمكينها من أداء مهامها بكل شفافية ونزاهة وحياد قبل وأثناء وبعد العملية الانتخابية.the Independent National Authority for Elections is a new permanent mechanism, created by the Algerian legislator under the Organic Law 19 - 07, with the aim of ensuring the transparency and integrity of the electoral process throughout all its stages, starting from reviewing the electoral lists to the end of the announcement of the results. The Algerian legislator has allocated the independent authority with wide and unlimited powers that include supervision and regulation And control over the electoral process and its compliance with legal provisions. The Algerian legislator has granted this authority a set of guarantees to enable it to perform its duties with full transparency, integrity and impartiality before, during and after the electoral process.
مذكرة ماستر
Keywords: السلطة الوطنية المستقلة للانتخابات – الانتخابات – الصلاحيات – رئيس السلطة – الأعضاء - الدستور; Autorité électorale nationale indépendante - Élections - Pouvoirs - Chef de l'autorité - Membres - Constitution